RELIGIOUS-POLITICAL CONFLICT BETWEEN BUDDHISTS AND ROHINGYA MUSLIMS IN MYANMAR - Djogatovic, Veljko (Political Review, 2023)
In Southeast Asia, there is a conflict between the Buddhist community living in the western part of Indochina and the Muslim minority – the Rohingya Muslims. Although this conflict is essentially religious, it is most often labeled as inter-ethnic, that is, as a type of civil war. This paper aims to present the religious side of this conflict and to point out the obvious mistake in qualifying it as exclusively inter-national and not inter-religious. Given the significant degree of interweaving of religion and politics in this particular case, the positions of both sides in the conflict, their basic ideas, goals and promoters, as well as the importance of the international factor, will be analyzed from the point of view of political science of religion. The first part of the paper will serve to present this religious-political conflict, both through its historical development and through its current state. The second part of the paper will analyze the participation of religious and religio-political organizations in this conflict. The third part of the paper will be devoted to the analysis of the influence of the international factor on the escalation and (potential) resolution of this conflict. Finally, the last chapter will serve to present the insights obtained through this research and will point to potential solutions for successfully overcoming of this conflict.